2021
DOI: 10.21037/atm-21-4059
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of crystal dissolution in gout during urate-lowering therapy with computer-aided MicroPure imaging: a cohort study

Abstract: Background: To evaluate whether MicroPure imaging, an ultrasound (US) image-processing technique with computer-aided analysis, can quantitatively detect crystal dissolution during urate-lowering therapy (ULT) in gout.Methods: This was a prospective study of gout patients requiring ULT. The first metatarsophalangeal joints were examined using US and MicroPure before and after 3 months of ULT. Elementary lesions of gout, including the double contour sign (DCS), aggregates, tophi, erosion, and other US features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…With regard to the studies investigating US, 8/8 (100%) reporting on the DC sign showed a reduction after 3–12 months, 5/6 (83.3%)63–67 reporting on aggregates showed a reduction after 3–12 months and 8/10 (80%)63 64 66 68–72 reporting on tophi showed a reduction after 3 months to 4 years. Four out of five studies (80%) reporting on inflammation (power Doppler (PD), grey scale, synovial thickness or Global OMERACT-European Alliance of Associations for Rheumatology (EULAR) Synovitis Score)64 65 67 73 found a significant change after 3–12 months. The single study revealing no significant result assessed PD score after 4 weeks only 74.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…With regard to the studies investigating US, 8/8 (100%) reporting on the DC sign showed a reduction after 3–12 months, 5/6 (83.3%)63–67 reporting on aggregates showed a reduction after 3–12 months and 8/10 (80%)63 64 66 68–72 reporting on tophi showed a reduction after 3 months to 4 years. Four out of five studies (80%) reporting on inflammation (power Doppler (PD), grey scale, synovial thickness or Global OMERACT-European Alliance of Associations for Rheumatology (EULAR) Synovitis Score)64 65 67 73 found a significant change after 3–12 months. The single study revealing no significant result assessed PD score after 4 weeks only 74.…”
Section: Resultsmentioning
confidence: 95%
“…The single study revealing no significant result assessed PD score after 4 weeks only 74. Two studies assessed change in erosions after 3 and 6 months, respectively, and found no significant differences64 67 (online supplemental table 3).…”
Section: Resultsmentioning
confidence: 98%